Laser‐assisted photodynamic therapy for superficial basal cell carcinoma and Bowen's disease: a randomized intrapatient comparison between a continuous and a fractional ablative CO2 laser mode. (17th July 2018) - Genouw, E.; Verheire, B.; Ongenae, K.; De Schepper, S.; Creytens, D.; Verhaeghe, E.; Boone, B.
Abstract: Background: Laser‐assisted photodynamic therapy is being explored as a method to enhance efficacy of photodynamic therapy (PDT). Objective: To compare a continuous (CL) and a fractional (FL) ablative CO2 laser‐assisted methyl aminolevulinate (MAL) PDT in the management of superficial basal cell carcinoma (sBCC) and Bowen's disease (BD). Methods: Thirty treatment areas in fifteen patients with inoperable, histologically verified sBCC or BD received CL or FL after intrapatient randomization. Laser treatment was followed by MAL application and illumination occurred 3 h later. This treatment was repeated after 2 weeks. An equivalence analysis was performed on the primary endpoint efficacy, while secondary endpoints pain, side‐effects and aesthetics were evaluated using paired samples tests. Patients were also asked for their preferred treatment. Results: An excellent efficacy of 92.9% (sBCC, 100%; BD, 80%) was found in both CL + PDT and FL + PDT after 12 months. Equivalence could not be established. Little pain was perceived in most patients during PDT illumination. PDT treatment in FL + PDT was less painful, significantly during the second treatment ( P  = 0.026). Side‐effects were mild to moderate with erythema being the most frequent immediate side‐effect, followed by oedema, crusting and burning sensation. Pigmentary changes occurred in 21% (CL + PDT) to 29% (FL + PDT), and aesthetics were good to excellent in all patients. CL + PDT and FL + PDT did not significantly differ in side‐effects ( P  = 0.219–1.000) or aesthetics ( P  = 0.157–1.000). Conclusions: Results in this pilot study support the promising role of laser‐assisted PDT. Both treatment arms demonstrated the same efficacy as well as comparable side‐effects and aesthetics. PDT illumination was significantly less painful in the FL + PDT group, suggesting a preference for FL + PDT. The authors recommend further investigation with a larger sample size, a subgroup analysis between sBCC and BD and comparison of different treatment protocols before one technique could be preferred to another.